2010
DOI: 10.1089/end.2008.0601
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Partial Nephrectomy: Evaluation of Learning Curve for an Experienced Renal Surgeon

Abstract: "Robot-assisted partial nephrectomy: Evaluation of learning curve for an experienced renal surgeon." Journal of Endourology.24,1. 57-61. (2010 Conclusions: The learning curve for RAPN is short for surgeons already experienced with LPN. The learning curve for portions performed under warm ischemia is slightly longer, implying that the critical portions of the procedure require more experience to become facile. Tumor size does not appear to have a significant impact on the learning curve for surgeons experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 23 publications
3
56
2
Order By: Relevance
“…24 Other authors have suggested a 25-case experience concerning the WIT. 22,25 Our findings tended to confirm this short learning curve, with rapid improvement of operative parameters and a trend towards lower complication rates. The literature also suggested that the transition from pure laparoscopic to RALPN may be faster in experienced laparoscopic surgeons.…”
Section: Discussionsupporting
confidence: 60%
“…24 Other authors have suggested a 25-case experience concerning the WIT. 22,25 Our findings tended to confirm this short learning curve, with rapid improvement of operative parameters and a trend towards lower complication rates. The literature also suggested that the transition from pure laparoscopic to RALPN may be faster in experienced laparoscopic surgeons.…”
Section: Discussionsupporting
confidence: 60%
“…Scores of [8][9] have been shown to have 14-fold risk and scores > 10 were associated with a 30-fold increase risk of complications compared to those patients reporting scores of 6 to 7 [6].…”
Section: Analyse the Impact Of Case MIX On The Rpn Lcmentioning
confidence: 99%
“…In their recent analysis of 38 consecutive RAPN cases, Haseebuddin et al found that the learning curve was 26 cases with respect to WIT and only 16 cases in regard to total operative time [25]. Surprisingly, parameters such as tumor complexity, intraoperative blood loss, and tumor size did not significantly shape the surgeon's learning curve [25].…”
Section: Learning Curvementioning
confidence: 99%